Expression of Personal Spiritual Concepts in Uzbek Proverbs (Zien Journal of Social Sciences and Humanities, 2023)
This article describes the expression of the concepts of personal spirituality in Uzbek folk proverbs. the specific meanings of concepts denoting the spirituality of a person in folk proverbs are proved based on examples taken from artistic works. It has been scientifically proven that proverbs show the rich cultural-educational, socio-economic, and spiritual image of the people.